The Main Problems in the Way of Learning English - Odiljonovna, Kurbanova Zarina; Erkinovna, Xikmatulloyeva Munisaxon (Miasto Przyszłości, 2023)
English has become the most popular language in use all around the world. However, in the way of learning this language non-native speakers may encounter several problems. In this article will be given top five frequent issues, with which majority of individuals definitely encounter while they study English. Of course, this article will give advice on how to overcome these difficulties.All given advices can help to improve your knowledge and speech in English.